Karakteristik Antibakteri Nanoceria-Kitosan yang disintesis menggunakan Metode Presipitasi - Muhammad Danu Rizkia; Iis Nurhasanah (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
CeO2 nanoparticles (nanoceria) is a material that posseses antibacterial activity. In this study, nanoceria was combined with chitosan to increase its antibacterial property. The formation of nanoceria-chitosan was analyzed using X-ray diffractometer, Fourier Transform Infrared (FTIR) and UV-Vis Spectrophotometer. The antibacterial activity of nanoceria-chitosan was tested using the disc diffusion method on Escherichia coli bacteria. X-ray diffraction pattern analysis showed that nanoceria-chitosan has a cubic structure. The incorporation of chitosan in nanoceria was identified at a wave number of 2919 cm-1 from the FTIR spectrum. Nanoceria-chitosan showed a smaller crystallite size, a larger energy band gap and better antibacterial activity than nanoceria.